Risk, health system and urban project - Matteraglia, Pierluigi (TeMA - Journal of Land Use, Mobility and Environment, 2020)
The article aims to establish the relationship between risk and the Veneto health system. The analysis of this report focused on vulnerability and resilience, highlights the critical aspects on which to focus the reorganization and strengthening measures (health presidium) to face new pandemics and / or health crises. The strengthening of the health system, which has strong relations with the city, is also analyzed from the point of view of the urban project. Comparing various localization alternatives.